Hydrogeochemistry and microbial contamination of groundwater from Lower Ponnaiyar Basin, Cuddalore District, Tamil Nadu, India - Jeevanandam, M.; Nagarajan, Ramasamy; Manikandan, M.; Senthilkumar, M.; Srinivasalu, S.; Prasanna, Mohan (Springer, 2012)
Groundwater is the major source of fresh water in regions where there is inadequate surface water resources. Forty-seven groundwater samples were collected from Lower Ponnaiyar basin, Cuddalore District, south India, during the premonsoon (PRM) and postmonsoon (POM) seasons of 2005. Out of 47 groundwater samples, 15 samples showing higher nitrate concentration were those collected during PRM 2005. Microbial analysis of these samples was carried out by employing 16S rRNA gene sequence tool. Detailed analysis was conducted to determine the hydrogeochemical processes and microbial contamination responsible for deterioration of quality. The abundance of the ions during PRM and POM are in the following order: Na > Ca > Mg > K = Cl > HCO3 > SO4 > CO3. The dominant water types in PRM are in the order of Na > Ca > Mg > K = Cl > mixed CaNaHCO3, whereas during POM NaCl > CaMgCl > mixed CaNaHCO3, and CaHCO3. However, NaCl and CaMgCl are major water types in the study area.The quality of groundwater in the study area is mainly impaired by surface contamination sources, mineral dissolution, ion exchange and evaporation. Groundwater chemistry was used to assess quality to ensure its suitability for drinking and irrigation, based on BIS and WHO standards. Suitability for irrigation was determined on the basis of the diagram of US Salinity Laboratory (USSL), sodium absorption ratio (SAR), residual sodium carbonate (RSC), and Na%. According to SAR and USSL classification, 27.66% (PRM) and 40.43% (POM) of samples fall under C3S2 category, indicating high salinity and medium sodium hazard, which restrict its suitability for irrigation. Microbiological analysis and its effects on the water quality were also addressed. The 16S rRNA gene sequences of 11 bacterial contaminants exhibited five groups with 11 operational taxonomic units with aerobic and facultatively anaerobic organisms. The presence of aerobic organisms in the groundwater samples reflects the active conversion of ammonia to nitrite by Nitrosomonas sp. which is further converted to nitrates by v other organisms. Further the presence of nitrate reducers could also play a role in the process of conversion of nitrate to ammonia and nitrate to molecular nitrogen.